Density and mintral content analysis of the bone tissue of the lower jaw and peculiarities of the posttraumatic dynamics. - Sohujko, R. R.; Masna, Z. Z.; Masna-Chala, O. Z.; Chelpanova, I. V. (Морфологія / Morphologia / Morfologìâ, 2019)
Background Bones fractures today occupy one of the prominent places among traumatic lesions. In dental practice, more than 50% of extractions of teeth are accompanied by the destruction of bone tissue of the alveolar areas of the jaws. A necessary condition for an adequate diagnosis of bone tissue quality deviations from the norm is the knowledge of the standard parameters of this indices, both intact bone and after surgical injury. As the quality of the bone tissue depends not only on its structure but also on the mineral content, the deficiency or excess of any of the mineral elements substantially changes the physical properties of the bone - strength, hardness, elasticity. Objective. The aim of our study was to determine the normative indices of the density of bone tissue of the lower jaw of the rat and its mineral content in intact animals, as well as to determine the regularities of the dynamics of these indices after surgical injury. Methods. The study was performed on 20 sexually mature, outbred male rats with a body weight of 180-200 g and a 3.5-month old age. The injury was modeled by breaking the integrity of the bone tissue of the mandible in the area of molars with the help of dental drill. The operation was performed under thiopental anesthesia. Control of the quality of bone tissue in the injured area of the mandible was performed using a dental radiovisiographer Siemens with the software Trophy Radiology. The unit of measurement of tissue density was taken to be the conventional unit of gravity (CUG). To determine the mineral content of the bone tissue of the rat's mandible, the method of atomic absorption spectral analysis (AASA) was used, which allowed to detect the contents of eight mineral elements (calcium (Ca), phosphorus (P), magnesium (Mg), sodium (Na ), potassium (K), iron (Fe), strontium (Sr), zinc (Zn)). Concentration of the investigated elements in bone tissue samples was indicated in mg/g. Investigation of the quality and mineral content of the bone tissue of the mandible was carried out in 1, 2 and 3 weeks after injury (5 animals at each time of the experiment), another 5 animals were in the control group. Results. The conducted study showed the presence of expressed dynamics of quality of the bone tissue of the mandible within three weeks after the bone injuries were caused. Within two weeks after injuries, the bone density of the mandible in the injured area gradually increases, increasing twice to the end of the second week compared to normal. During the third week after the injury, the investigated index is reduced, but remains slightly higher than in intact animals. The analysis of the mineral content of the bone tissue of the body of the mandible of the rat in norm and after the surgical trauma has made it possible to determine the quantitative content of all investigated mineral elements. Among the investigated macroelements, the largest proportion belongs to calcium, somewhat smaller phosphorus, the least significant are the proportion of sodium and magnesium. Among the studied microelements, the largest share belongs to potassium. The share of iron was somewhat lower, and the smallest were shares of strontium and zinc. Conclusion. Absolute indices of the content of the studied macro- and microelements have unexpressed dynamics for each element. Among all investigated mineral elements during the post-traumatic period, only phosphorus has a dynamics similar to that of bone density.